Analysis of Income Maintenance Efforts Among Traders in the Tourism Center - Hilmi, Irpan; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Lembaga Riset dan Inovasi Al-Matani, 2024)
The purpose of this research is to find out, analyze and explain how much income is obtained by traders in the tourism center of Mekar Buana Village, Tegalwaru District, Karawang Regency. The research method uses a qualitative descriptive approach. This research was conducted from June to July 2023 with the research location at the Mekar Buana Village Tourism Center. Tegalwaru Karawang Regency. The population was 15 people who were taken as a whole consisting of traders. Data collection techniques are through observation and interviews. The income analysis used is by comparing the income of traders on weekdays with income on holidays. The results showed that traders operating in the tourist area of Mekar Buana Village amounted to 15 traders with details of 3 traders operating every day and 12 traders operating only on holidays. The cycle of tourist visits affects the income of each trader where income on weekdays is only 25% and income on holidays ranges up to 75% of monthly income.